Investigation of a novel façade-based solar loop heat pipe water heating system - Wang, Zhangyuan (2012)
Solar thermal is one of the most cost-effective renewable energy technologies, and solar water heating is one of the most popular solar thermal systems. Based on the considerations on the existing barriers of the solar water heating, this research will propose a novel façade-based solar water heating system employing a unique loop heat pipe (LHP) structure with top-level liquid feeder, which will lead to a façade-integrated, low cost, aesthetically appealing and highly efficient solar system and has considerable potential to provide energy savings and reduce carbon emissions to the environment.